Verso il reale: schizofrenia/psicoanalisi - Pagliardini, Alex (Philosophy Kitchen - Rivista di filosofia contemporanea, 2018)
The paper aims to develop a path through Lacan’s teaching and writings upon the relationship between psychoanalysis and schizophrenia. Particularly, it wants to show the movement from Symbolic to Real, element present both in schizophrenia and in the psychoanalytic practice, although the highlighted structural divergence in this movement between two sides. The different articulations of subject between symbolic and real, living body and language/signifier, are here exposed through three paradigms inferred from Lacan’s teaching. Particular attention is devoted to the concept of pousse-à-la-femme (pushtowards- woman), introduced by Jacques Lacan through the figure of Schreber, as a paradigmatic condition of psychosis. In fact, this push is characterized by the movement towards Real and the exception of not-all and the feminine jouissance.